Peculiarities of cancer incidence in Tomsk region population (1990—2001) - L. F. Pisareva; Ye. L. Choynzonov; A. P. Boyarkina; I. N. Odintsova; V. D. Goldin; N. A. Martynova; R. M. Takhauov (Бюллетень сибирской медицины, 2003)
A cancer incidence in general and in its separate nosologic forms (stomach cancer, liver cancer, cancer of lung, skin cancer, breast cancer, cervical cancer, prostate cancer, thyroid gland cancer and hemoblastosis cancer) has been studied in the population of Tomsk and Tomsk region within 1990—2001 taking into account ages and sexes. The dynamics of the cancer incidence in general and in separate forms of malignant neoplasms has been cited and the prognosis of this process up to 2007 has been done. An analysis of the main risk factors has been made.